Audit Layanan Teknologi Informasi PT. XYZ Menggunakan Framework ITIL (Information Technology Infrastructure Library) - arien ferlina putri; Tristiyanto Tristiyanto; Yunda Heningtyas (Universitas Lampung, 2019)
PT. XYZ needs information technology to carry out all activities in presenting the latest news. Audit of information technology services is needed to determine the extent of information technology services in PT. XYZ. This study uses Information Technology Infrastructure Library (ITIL) framework to audit domain service operation of PT. XYZ. The focus of this research is on the domain service operation. Data from this study were obtained based on the results of interviews, observations and questionnaires. The results of the study found that the level of maturity of PT. XYZ in information technology services in the service operation domain of respondents was 3,1 (Defined) and the finding were worth 2 (Managed). This result is different from the expected because IT Lampung haven’t met the SOP criteria standards, especially in management incident reports and resolved. IT division also haven’t conducted user’s statisfaction survey about the IT service provided.